2011
DOI: 10.1186/1465-9921-12-96
|View full text |Cite
|
Sign up to set email alerts
|

Airway resistance at maximum inhalation as a marker of asthma and airway hyperresponsiveness

Abstract: BackgroundAsthmatics exhibit reduced airway dilation at maximal inspiration, likely due to structural differences in airway walls and/or functional differences in airway smooth muscle, factors that may also increase airway responsiveness to bronchoconstricting stimuli. The goal of this study was to test the hypothesis that the minimal airway resistance achievable during a maximal inspiration (Rmin) is abnormally elevated in subjects with airway hyperresponsiveness.MethodsThe Rmin was measured in 34 nonasthmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…On the basis of our study, and confirmed by other researches already quoted, a greater impairment of FEF 25-75 % seems to correspond to a more severe AHR 6,16,18,19. This is especially in line with the findings of Currie et al42 who compared asthmatic patients with borderline Mch measured AHR to those with moderate-to-severe AHR, where the latter had significantly lower FEF 25-75 % values.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the basis of our study, and confirmed by other researches already quoted, a greater impairment of FEF 25-75 % seems to correspond to a more severe AHR 6,16,18,19. This is especially in line with the findings of Currie et al42 who compared asthmatic patients with borderline Mch measured AHR to those with moderate-to-severe AHR, where the latter had significantly lower FEF 25-75 % values.…”
Section: Discussionsupporting
confidence: 93%
“…Results of our study are in accordance with other studies where impaired FEF 25-75 values are inversely related to airway AHR both in children and adults affected by rhinitis and/or asthma 14,15,16,17,18,19. Therefore, when facing a FEF 25-75 impairment associated with normal FEV1 and FEV1/FVC in patients with asthma symptoms, we are expected to think that AHR, and consequently asthma, may be present.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our methods applied a semiautomated approach to the segmentation of ventilated airspaces [ 30 ] leading to a novel index to quantify the degree of heterogeneity throughout the imaged lung. Hence, we can quantitatively relate such heterogeneity to alterations in dynamic mechanical lung function sensitive to airways, tissues, and the degree of heterogeneous constriction [ 3 , 20 , 21 , 33 , 34 , 36 ] as well as the overall reactivity (PC 20 ) [ 4 , 12 , 15 ]. Similar to prior studies [ 7 ], we found that both healthy subjects that withhold DIs and mild-to-moderate asthmatics bronchoconstricted when exposed to airway agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the included articles reported oscillometry (IOS/FOT) [22][23][24][25][26][27][28] and five reported MMEF. 23 29-31 None of the included studies reported MBW use in diagnosing asthma.…”
Section: Study Characteristicsmentioning
confidence: 99%